2004
DOI: 10.1177/0269881104047284
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with venlafaxine and carbamazepine in depressive patients not responding to venlafaxine: pharmacokinetic and clinical aspects

Abstract: The chiral antidepressant venlafaxine (VEN) is both a serotonin and a norepinephrine uptake inhibitor. CYP2D6 and CYP3A4 contribute to its metabolism, which has been shown to be stereoselective. Ten CYP2D6 genotyped and depressive (F32x and F33x, ICD-10) patients participated in an open study on the pharmacokinetic and pharmacodynamic consequences of a carbamazepine augmentation in VEN non-responders. After an initial 4-week treatment with VEN (195 +/- 52 mg/day), the only poor metabolizer out of 10 depressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 47 publications
1
9
0
2
Order By: Relevance
“…In another clinical pilot study, as an augmentation to citalopram treatment, carbamazepine has been found to be clinically effective in depressed patients with comorbid anxiety disorders [218]. Similar to this study, carbamazepine augmentation provided clinical improvement in the majority of depressed patients non-responsive to venlafaxine treatment [219].…”
Section: Evidence Of Antidepressant Efficacy Associated With Gabaergisupporting
confidence: 71%
“…In another clinical pilot study, as an augmentation to citalopram treatment, carbamazepine has been found to be clinically effective in depressed patients with comorbid anxiety disorders [218]. Similar to this study, carbamazepine augmentation provided clinical improvement in the majority of depressed patients non-responsive to venlafaxine treatment [219].…”
Section: Evidence Of Antidepressant Efficacy Associated With Gabaergisupporting
confidence: 71%
“…Gex-Fabry et al investigated 35 patients on chronic medication with 14 venlafaxine and they reported S/R concentration ratios between 0.4-2.5 (median 1.1) (GexFabry et al, 2004;Gex-Fabry et al, 2002). Ciusani and co-workers studied 5 patients receiving individually adapted doses between 75-225 mg/day and they found mean plasma S/R ratios of 1.16, 0.94 and 1.01 for venlafaxine, Odm-venlafaxine and Ndm-venlafaxine, respectively (Ciusani et al, 2004). Taken together, there seems to be both species differences and inter-individual variability in the S/R disposition that need to be considered when results from different studies are compared.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 A more plausible explanation is the fact that patients can also be non-responders to venlafaxine therapy, not linked to a certain CYP450 genotype, but in combination with a poor metabolizer the risk of a maintained depression and acquiring ADRs is increased substantially. 8,20 Other more rare ADRs include pulmonary (e.g. interstitial pneumonia) and cardiovascular (e.g.…”
Section: Discussionmentioning
confidence: 99%